FISTULOGRAPHY IN THE DIAGNOSIS AND TREATMENT OF FISTULAS NECK - Tkachenko, P.; Rezvina, K. (World of Medicine and Biology, 2016)
Fistula – abnormal channel that connects the deeper layers of tissue or hollow bodies from the outer surface of the body (skin or mucosa) or submitted tyazhystymy entities or their individual chambers interconnected. Given this, they are divided into external and internal. Depending on the placement of internal tissue end fistula, the latter may be blind or penetrating, penetrating into the cavity of some internal organs (pharynx, intestine, biliary or urinary tract).Fistula are congenital and acquired. Congenital fistula always lined epithelium (endothelium) and acquired - mostly consisting of granulation tissue, sometimes with epithelium. They arise due to violation of the formation during embryogenesis, that there are anomalies or malformations. The largest number of them in a dental practice make fistula lateral neck connecting the throat to the skin.
Keywords: neck; dermoid cyst; epidermoid cyst; fistula; fistulography